2007
DOI: 10.1007/s11259-007-9002-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic management of copper deficiency in buffalo heifers: Impact on immune function

Abstract: To evaluate the magnitude of copper deficiency in Northern India and to examine the various haematobiochemicals, enzymes, vitamins and immune functions affected by copper deficiency, and to identify the parameters which can be of diagnostic importance in copper deficiency, a survey was conducted in 12 districts of Northern India. Significant deficiency of copper was observed in soil, fodder and serum samples of buffalo heifers. Fifty hypocuperaemic buffalo heifers were selected from these areas and were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…During the transition period, several disorders can occur at different intensities, such as oxidative stress (Lykkesfeldt and Svendsen 2007), and therefore, in this study, mineral supplementation had a beneficial effect (increased antioxidant and reduced ROS), which minimized this oxidative stress in lactating cows. The subcutaneous mineral supplementation was able to stimulate the SOD enzyme increasing the activity since copper administered in cows act as a cofactor of this enzyme (Sharma et al 2008). In similar studies using diet supplementation also reported an increase in SOD activity, when copper was one of the minerals supplemented (Spears and Weiss 2008, Sordillo and Aitken 2009, Machado et al 2014.…”
Section: Discussionmentioning
confidence: 85%
“…During the transition period, several disorders can occur at different intensities, such as oxidative stress (Lykkesfeldt and Svendsen 2007), and therefore, in this study, mineral supplementation had a beneficial effect (increased antioxidant and reduced ROS), which minimized this oxidative stress in lactating cows. The subcutaneous mineral supplementation was able to stimulate the SOD enzyme increasing the activity since copper administered in cows act as a cofactor of this enzyme (Sharma et al 2008). In similar studies using diet supplementation also reported an increase in SOD activity, when copper was one of the minerals supplemented (Spears and Weiss 2008, Sordillo and Aitken 2009, Machado et al 2014.…”
Section: Discussionmentioning
confidence: 85%
“…The results obtained are opposite with observations by Gengelbach, Ward, and Spears () and Spears, ; who showed that supplementation of cattle feed with copper sulphates did not affect the concentration of pro‐inflammatory cytokines TNF‐α and IL‐1. It may indicate also non‐physiological serum concentration of this cytokine prior to feed supplementation (Scuderi, ; Sharma, Joshi, & Das, ).…”
Section: Discussionmentioning
confidence: 99%
“…The serum concentrations of Zn and Cu were measured by atomic absorption spectrophotometer (Shimadzo AA-670; Shimadzo, Japan) followed by a digestion with nitric acid [9].…”
Section: Zinc and Copper Concentrationmentioning
confidence: 99%
“…Cu plays an important biological role as a cofactor for several Cu-dependent enzymes [9]. Likewise, Zn is essential for the activity of a large number of enzymes, including those involved in the synthesis of DNA and RNA, cellular replication, and proliferation in the animal body [10].…”
mentioning
confidence: 99%